Speed breeding 3.0: mainstreaming light-driven plant breeding for sustainable genetic gains - Kabade, Pramod Gorakhanath; Kumar, Sanjay; Kohli, Ajay; Singh, Uma Maheshwar; Sinha, Pallavi; Singh, Vikas Kumar (Cell Press, 2025)
Advances in photobiological tools are revolutionizing plant breeding by enabling precise control of light parameters, addressing yield stagnation, and mitigating climate challenges. Full-spectrum light-emitting diodes (LEDs) and optimized light protocols have significantly reduced breeding cycles. This review highlights light-driven strategies that are accessible and practical for plant breeders world-wide including the role of light spectrum, intensity, and photoperiod in acceleration of plant growth in both short- and long-day crops. Speed breeding 3.0, with tailored rapid generation advancement (RGA) protocols designed for diverse crop populations, has the potential to significantly sustain genetic gains in a more efficient and targeted manner. These innovative approaches hold the potential to transform global agriculture and secure food systems in the face of rising populations and environmental uncertainties.